Granules and preparations using the same
By placing molten constituent layers on the surface of the nuclear material and placing a raw material containing layer on the surface of the melting constituent layer, the content and particle size uniformity of the raw material are improved, and the low content and uneven particle size of the raw material in the prior art are solved. The problem is that the efficient production of the preparation and good medication performance have been achieved.
Patent Information
- Application Number
- CN202180018225.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-11
- Filing Date
- 2021-03-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-03-09
AI Technical Summary
The existing melt granulation method is difficult to control the particle size and it is difficult to increase the content of raw materials in the granulated substances, resulting in a reduction in the overall preparation and drug compliance.
Using a particle structure including a nuclear material, a melting component layer and a raw material layer, the content of the raw material and the content of the raw material and the Particle size uniformity.
The improvement of the content of raw materials and the uniformity of particle size are achieved, and the problem of large-scale preparations and reduced compliance with medication is solved.
Smart Images

Figure CN115209877B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to granules containing high content of raw material drugs and preparations using the granules. Background Art
[0002] In order to improve the manufacturability of pharmaceutical preparations, active pharmaceutical ingredients are granulated with various additives. Granulation methods can be divided into wet granulation and dry granulation according to the presence or absence of solvents. When granulating water-unstable active pharmaceutical ingredients, dry granulation methods without using solvents are selected. In dry granulation methods, melt granulation methods in which additives are heated and melted and used as binders are also widely known. For example, Patent Documents 1 to 4 and Non-Patent Document 1 describe core particles in which a layer containing an active pharmaceutical ingredient is arranged on the surface of a core substance by a melt granulation method.
[0003] On the other hand, the melt granulation method is greatly affected by the physical properties of the molten component, so it is difficult to control the particle size of the granulated product. In addition, since the melt granulation method uses the molten component instead of the solvent, it is difficult to increase the content of the raw material in the granulated product, which will inevitably lead to the problem of large-scale preparations and reduced medication compliance.
[0004] (Prior art literature)
[0005] (Patent Document)
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-1999
[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-199721
[0008] Patent Document 3: Japanese Patent Application Publication No. 2015-71542
[0009] Patent Document 4: Japanese Patent Application Laid-Open No. 6-256169
[0010] (Non-patent literature)
[0011] Non-patent document 1: Chem. Pharm. Bull. 65, 726-731 (2017) Summary of the invention
[0012] (Problems to be solved by the invention)
[0013] An object of one embodiment of the present invention is to provide granules with high API content and high particle size uniformity by melt granulation. Alternatively, an object of one embodiment of the present invention is to provide a preparation containing granules with high API content and high particle size uniformity.
[0014] (Measures taken to solve the problem)
[0015] According to one embodiment of the present invention, a particle is provided, which includes: a core material; a molten component layer configured on the surface of the core material; and a raw material drug-containing layer configured on the surface of the molten component layer, the molten component layer includes a first molten component, the raw material drug-containing layer includes the raw material drug, and also includes a second molten component or a polymer that is compatible with the first molten component.
[0016] The second molten component may have a melting point lower than the melting point of the first molten component and 100° C. or lower.
[0017] The second molten component may have a melting point higher than the melting point of the first molten component and 100° C. or lower.
[0018] When the first molten component is stearic acid or lauromacrogol, the compatible polymer is selected from the group consisting of aminoalkyl methacrylate copolymers, ammonioalkyl methacrylate copolymers, methacrylic acid copolymers, hydroxypropyl methylcellulose acetate succinate, and polyvinyl pyrrolidone.
[0019] The core material is spherical, and the particle size of the core material can be larger than the particle size of the raw material, the particle size of the first molten component and the particle size of the second molten component.
[0020] The core material has pores on the surface, and the molten component layer may have a structure in which the first molten component is also arranged in the pores.
[0021] According to one embodiment of the present invention, a preparation comprising any one of the particles and one or more pharmaceutically acceptable additives is provided.
[0022] The additive may be a disintegrant.
[0023] (Effects of the Invention)
[0024] According to one embodiment of the present invention, a granule having a high API content and high particle size uniformity is provided. Alternatively, according to one embodiment of the present invention, a preparation is provided, comprising granules having a high API content and high particle size uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a schematic diagram showing a particle including a core particle according to one embodiment of the present invention.
[0026] Figure 2 is a schematic diagram showing a particle including a core particle according to one embodiment of the present invention.
[0027] Figure 3 The flowchart is for explaining a method for producing particles including core particles according to one embodiment of the present invention.
[0028] Figure 4 The flowchart is for explaining a method for producing particles including core particles according to one embodiment of the present invention.
[0029] Figure 5 (a) is a scanning electron microscope (SEM) image of the particles of Example 1, (b) is a SEM image of the particles of Example 2, (c) is a SEM image of the particles of Example 3, (d) is a SEM image of the particles of Example 4, (e) is a SEM image of the particles of Comparative Example 1, and (f) is a SEM image of the particles of Comparative Example 2. DETAILED DESCRIPTION
[0030] Hereinafter, the granules of the present invention and the preparations using the granules will be described with reference to the accompanying drawings. Note that the granules of the present invention and the preparations using the granules are not limited to the description of the embodiments and examples shown below. In addition, in the drawings referred to in the present embodiment and the examples described later, the same reference numerals are given to the same parts or parts having the same functions, and their repeated descriptions are omitted.
[0031] Figure 1 The granule 10 is a schematic diagram (cross-sectional view) showing a granule 10 according to one embodiment of the present invention. The granule 10 includes a core material 11 , a molten component layer 13 disposed on the surface of the core material 11 , and a drug substance-containing layer 15 disposed on the surface of the molten component layer 13 .
[0032] The core material 11 is a carrier for configuring the molten component layer 13 and the raw material drug-containing layer 15, and is a core material for configuring the molten component layer 13 and the raw material drug-containing layer 15 when preparing the granules 10. In order to obtain close adhesion with the molten component layer 13, an adsorbent is used as the core material 11. As the core material 11, an adsorbent such as Amberlite IRP-64, ion exchange resin, kaolin, carboxymethylcellulose calcium, hydrous silicon dioxide, magnesium silicate, light silicic anhydride, light liquid paraffin, diatomaceous earth, synthetic aluminum silicate, aluminum oxide, aluminum hydroxide, cotton wool, magnesium carbonate, precipitated calcium carbonate, dextrin, silicon dioxide, composite potassium aluminum silicate particles, bentonite, polyethylene fiber, magnesium aluminum silicate, medicinal charcoal, etc. can be used.
[0033] The core material 11 is preferably spherical in shape to uniformly arrange the molten component layer 13 and the API-containing layer 15. In addition, from the perspective of API adhesion, the particle size of the core material 11 should be larger than the particle size of the API. The particle size of the core material 11 is, for example, more than twice the particle size of the API, but is not limited thereto.
[0034] The molten component layer 13 is a layer disposed between the core material 11 and the API-containing layer 15. The molten component layer 13 is a bottom layer for disposing the API-containing layer 15. In the above patent document, the molten component and the API are directly disposed on the core material, but when the API itself has weak adhesion to the core material or the core material has poor ability to carry the API, it is necessary to add more molten component relative to the API, and it is impossible to obtain particles containing a high content of API. In contrast, in the present invention, in the particle 10, the molten component layer 13 is disposed on the surface of the core material 11, so that more APIs are attached to the molten component layer 13, thereby effectively increasing the content of APIs in the particle 10.
[0035] As described above, the molten component (first molten component) constituting the molten component layer 13 is selected from an oily additive. In order to form the molten component layer 13 by the melt granulation method, the first molten component is selected from an additive that is solid at room temperature. Taking into account the temperature range commonly used in the melt granulation method, the first molten component is preferably selected from an additive having a melting point below 100°C, and is preferably selected from an additive having a melting point within a temperature range where denaturation of the raw material drug or a significant increase in similar substances is not found. Examples of additives having such characteristics include glycerol monostearate, macrogol (i.e., polyethylene glycol), lauromacrogol, and stearic acid, but are not limited thereto. In addition, the first molten component is preferably selected from an additive that does not denature the raw material drug or significantly increase the confirmation of similar substances due to contact with the raw material drug.
[0036] The molten component layer 13 can be arranged on the surface of the core material 11 in an amount capable of configuring the drug-containing layer 15, and can be arranged on at least a portion of the surface of the core material 11. The molten component layer 13 preferably covers more than 90% of the surface of the core material 11, and more preferably covers the entire surface of the core material 11. The thickness of the molten component layer 13 is not particularly limited, but from the viewpoint of increasing the content of the drug-containing substance 10 in each particle, it is preferred that the thickness of the molten component layer 13 is as thin as possible. In one embodiment, the first molten component constituting the molten component layer 13 is also preferably arranged in the pores that the core material 11 has on its surface. In one embodiment, the interface between the core material 11 and the molten component layer 13 may have a structure in which the molten component constituting the molten component layer 13 enters from the surface of the core material 11. In this case, the core material 11 and the molten component layer 13 may not have a clear interface. The molten component is arranged not only on the surface of the core material 11 but also in the pores connected to the surface of the core material 11 , so that the molten component layer 13 has an anchoring effect on the core material 11 , thereby improving the adhesion of the molten component layer 13 to the core material 11 .
[0037] The drug substance-containing layer is a layer containing the drug substance and the second molten component or the polymer, and is disposed on the surface of the molten component layer 13 . Figure 1 The drug substance-containing layer 15 is shown to contain particles 10 of the drug substance and the second melt component. Figure 2 Granule 20 is shown, in which the drug substance-containing layer 25 contains the drug substance and a polymer having compatibility with the first molten component. In granules 10 and 20, the drug substance is not particularly limited. In the method of preparing granules 10 and 20, since no solvent, particularly water, is used, a drug substance that is unstable to water can be appropriately used.
[0038] In the drug-containing layer 15, the second molten component is an additive for bonding the drug-containing materials to each other and to bond the drug-containing materials to the surface of the molten component layer 13. In order to form the drug-containing layer 15 by the melt granulation method, the second molten component is selected from additives that are solid at room temperature. Considering the temperature range commonly used in the melt granulation method, the second molten component is preferably selected from additives having a melting point below 100°C, and preferably selected from additives having a melting point within a temperature range where no denaturation of the drug-containing material or a significant increase in the like is found. In addition, when an additive having a melting point lower than that of the first molten component is selected as the second molten component, the drug-containing layer 15 can be formed by the melt granulation method, and the drug-containing layer 15 can be arranged on the surface of the molten component layer 13 without having a significant effect on the surface structure of the molten component layer 13 or changing the surface structure of the molten component layer 13. On the other hand, when an additive having a higher melting point than the first melting component is selected as the second melting component, when the API-containing layer 15 is formed by the melt granulation method, the surface of the melting component layer 13 is slightly melted, so that the interface between the melting component layer 13 and the API-containing layer 15 is fused, thereby improving the adhesion of the API-containing layer 15 to the melting component layer 13.
[0039] As additives used as the second molten component, for example, stearic acid, glycerol monostearate, polyethylene glycol (macrogol, i.e., polyethylene glycol), carnauba wax, hardened oil, lauroyl alcohol, palmitic acid and cetyl alcohol can be cited, but are not limited thereto. The second molten component is preferably selected from additives that will not denature the raw material drug or confirm a significant increase in similar substances due to contact with the raw material drug. From the perspective of attachment to the core material 11, the particle size of the molten component needs to be smaller than the particle size of the core material 11. In addition, the molten component (second molten component) contained in the raw material drug-containing layer 15 can be the same additive as the molten component (first molten component) contained in the molten component layer 13, or it can be different.
[0040] In one embodiment, in the particles 20, a polymer that is compatible with the first molten component can be used instead of the second molten component. The polymer has "compatibility" with respect to the first molten component, which means that the first molten component and the polymer are not separated. Alternatively, it indicates the state in which the polymer is dispersed in the first molten component, or it indicates the state in which the first molten component is dispersed in the polymer. In one embodiment, the state in which the molten component and the polymer are not separated can be confirmed by the increase in the viscosity of the mixture (liquid or semi-solid with fluidity) when the molten component is melted by mixing the molten component and the polymer. By using a polymer that is compatible with the first molten component, the viscosity of the surface of the molten component layer 13 is further improved compared to the use of the second molten component, and the drug-containing layer 25 can be more stably attached. As a combination of polymers that are compatible with the first molten component, when the first molten component is stearic acid or lauromacrogol, it is preferred to combine aminoalkyl methacrylate copolymers, ammonium methacrylate copolymers, methacrylic acid copolymers, hydroxypropyl methylcellulose acetate succinate or polyvinyl pyrrolidone as polymers. More preferably, when the first melting component is stearic acid, aminoalkyl methacrylate copolymer, ammonioalkyl methacrylate copolymer or polyvinyl pyrrolidone can be combined as the polymer. Alternatively, when the first melting component is lauromacrogol, aminoalkyl methacrylate copolymer, ammonioalkyl methacrylate copolymer, methacrylic acid copolymer or hydroxypropyl methylcellulose acetate succinate can be preferably combined.
[0041] When a polymer compatible with the first molten component is used instead of the second molten component, the content of the first molten component is preferably greater than the content of the polymer in the pellet 20. For example, in the pellet 20, the mixing ratio of the first molten component to the polymer is preferably 20:1 to 1:1, more preferably 4:1 to 1:1.
[0042] The drug-containing layer 15 and the drug-containing layer 25 contain the drug-containing substance as a main component. In the drug-containing layer 25, it is preferred that 50% by mass or more of the drug-containing substance is contained relative to the total mass of the drug-containing substance and the second molten component or polymer. In other words, in the drug-containing layer 15 and the drug-containing layer 25, it is preferred that a small amount of the second molten component or polymer is contained within the range in which the drug-containing layer 15 or the drug-containing layer 25 can be formed on the surface of the molten component layer 13. Thus, the drug-containing content in the granules 10 and 20 can be effectively increased.
[0043] [Method for producing the particle 10]
[0044] Figure 3It is a flowchart of a method for manufacturing particles containing core particles according to an embodiment of the present invention. The core material 11 and the first molten component 131 are mixed (S101), and the first molten component 131 is arranged on the surface of the core material 11. In addition, the first molten component 131 is melted by a melt granulation method to form a molten component layer 13 on the surface of the core material 11 (S103). At this time, the core material 11 and the first molten component 131 are heated to a temperature above the melting point of the first molten component 131. Considering the temperature range generally used in the melt granulation method, the heating temperature is below 100°C. In addition, preferably, the first molten component 131 is arranged not only on the surface of the core material 11, but also in the pores connected to the surface of the core material 11, thereby giving the molten component layer 13 an anchoring effect on the core material 11 and improving the adhesion of the molten component layer 13 to the core material 11.
[0045] The core material 11 with the molten component layer 13 is mixed with the API 151 and the second molten component 153 (S105), and the API 151 and the second molten component 153 are arranged on the surface of the molten component layer 13. In addition, the second molten component 153 is melted by the melt granulation method to form the API-containing layer 15 on the surface of the molten component layer 13 (S107). At this time, the core material 11 with the molten component layer 13, the API 151 and the second molten component 153 are heated to a temperature higher than the melting point of the second molten component 153. Considering the temperature range generally used in the melt granulation method, the heating temperature is 100°C or less.
[0046] In one embodiment, when an additive having a lower melting point than the first melting component 131 is selected as the second melting component 153, when the API-containing layer 15 is formed by the melt granulation method, the API-containing layer 15 can be formed on the surface of the molten component layer 13 by heating to a temperature higher than the melting point of the second melting component 153 and lower than the melting point of the first melting component 131, without having a significant effect on the surface structure of the molten component layer 13 or changing the surface structure of the molten component layer 13. On the other hand, when an additive having a higher melting point than the first melting component 131 is selected as the second melting component 153, when the API-containing layer 15 is formed by the melt granulation method, the surface of the molten component layer 13 is slightly melted by heating to a temperature higher than the melting point of the second melting component 153, so that the interface between the molten component layer 13 and the API-containing layer 15 is fused, and the adhesion of the API-containing layer 15 to the molten component layer 13 can be improved. In addition, it is preferable to perform melt granulation within a temperature range in which the API 151 is not denatured or a significant increase in the number of related substances is not observed.
[0047] [Method for Preparing Particles 20]
[0048] As described above, a polymer having compatibility with the first molten component may be used instead of the second molten component 153 . Figure 4 1 is a flowchart illustrating a method for preparing a core-containing particle 20 according to an embodiment of the present invention. The process until the molten component layer 13 is formed on the surface of the core material 11 (S103) is the same as the process for preparing the particle 10, and thus detailed description is omitted.
[0049] The core material 11 configured with the molten component layer 13 is mixed with the raw material drug 151 and the polymer 253 having compatibility with the first molten component (S205), and the raw material drug 151 and the polymer 253 are arranged on the surface of the molten component layer 13. In addition, the first molten component 131 is melted by the melt granulation method to form a raw material drug-containing layer 25 on the surface of the molten component layer 13 in which the raw material drug 151 and the polymer 253 are dispersed in the first molten component 131 (S207). At this time, the core material 11 configured with the molten component layer 13, the raw material drug 151 and the polymer 253 are heated to a temperature higher than the melting point of the first molten component 131. Considering the temperature range generally used for the melt granulation method, the heating temperature is 100°C or less.
[0050] In the present embodiment, the first molten component 131 located on the surface of the molten component layer 13 is melted, and the API 151 and the polymer 253 are dispersed on the surface of the molten component layer 13, thereby forming the API-containing layer 25. In the present embodiment, since the polymer 253 is compatible with the first molten component, the API 151 and the polymer 253 are not separated from the first molten component 131, and the API-containing layer 25 can be formed. In the present embodiment, by using a polymer that is compatible with the first molten component, the viscosity of the surface of the molten component layer 13 is further increased compared to when the second molten component is used, and the API-containing layer 25 can be attached more stably.
[0051] [preparation]
[0052] The granules 10 or 20 can be used to prepare a preparation. For example, the granules 10 or 20 can be mixed with one or more known pharmaceutically acceptable additives to prepare a pharmaceutical composition. In addition, the pharmaceutical composition can be compressed into a tablet. In addition, the pharmaceutical composition to which a disintegrant is added can be compressed into an orally disintegrating tablet. In addition, the pharmaceutical composition can be encapsulated in a capsule as a capsule.
[0053] Example
[0054] [Example 1]
[0055] Hydrous silica (Fuji Silysia Chemical Ltd., Sylopure (registered trademark) P100) was used as the core material, and monostearate glycerol (RIKEN VITAMIN Co., Ltd., RIKEMAL (registered trademark) S-100P) was used as the first molten component. 300 g of hydrous silica and 480 g of monostearate glycerol were placed in a high-speed stirring granulator (Fukae Industrial Co., Ltd., high-speed mixer, FS-GS-5J), and granulated for 11 minutes under the conditions of a stirrer speed of 300 rpm, a chopper speed of 1500 rpm, and a water temperature of 75.0°C to 79.0°C. At this time, the temperature of the additive was 69.5°C to 73.0°C.
[0056] 195.0 g of the core material with the obtained molten component layer arranged on the surface, 372.2 g of Sitagliptin Phosphate as a raw material drug, and 27.0 g of stearic acid (NOF Corporation, plant) as a second molten component were put into a high-speed stirring granulator (Fukae Industry Co., Ltd., high-speed mixer, FS-GS-5J), and granulation was carried out for 22 minutes under the conditions of a stirrer speed of 150 rpm to 300 rpm, a chopper speed of 1500 rpm, and a water temperature of 74.9° C. to 75.0° C. At this time, the temperature of the additive was 68.4° C. to 70.3° C.
[0057] The scanning electron microscope (SEM) images of the particles were obtained. Figure 5 (a) is shown. In addition, the particle size of the particles was measured. The particle size measurement was performed using a laser diffraction scattering method measurement device (Beckman Coulter Inc., LS 13 320). The measured particle size is shown in Table 1.
[0058] [Example 2]
[0059] As Example 2, a core material having a molten component layer of Example 1 on its surface was used and melt granulation was performed using a tumbling granulator. 97.5 g of the core material having a molten component layer of Example 1 on its surface, 186.1 g of sitagliptin phosphate as a raw material, and 22.5 g of stearic acid (NOF Corporation, plant) as a second molten component were placed in a rotary granulator (Powrex Corporation, MP-01), and granulation was performed for 105 minutes at a rotor speed of 200 rpm to 500 rpm, an air supply volume of 0.40 L / min to 0.55 L / min, and an air supply temperature of 89.5°C to 90.9°C. At this time, the temperature of the additive was 55.4°C to 65.7°C.
[0060] The SEM images of the obtained particles are shown in Figure 5 In addition, the particle size of the particles of Example 2 is shown in Table 1.
[0061] [Table 1]
[0062]
[0063] Obviously, the content ratio of the raw material drug in the granules of Example 1 and Example 2 is about 60%, which can achieve a higher content. In addition, Figure 5 (a) and Figure 5 The results of (b) show that the particles of Examples 1 and 2 are round particles, and the particle size uniformity is high due to the use of core materials. Figure 5 (a), it can be confirmed that the particles in Example 1 have uneven surfaces. The particles in Example 1 having uneven surfaces can be expected to have improved water conductivity. Figure 5 (b) Since the surface of the particles in Example 2 is smooth, coating can also be considered.
[0064] [Nuclear Matter Research]
[0065] In the manufacturing method of Example 1, the core material was changed to form a molten component layer on the surface of the core material. As hydrous silica, FujiSil (registered trademark) of Fuji Chemical Industry Co., Ltd. was used, as magnesium aluminometasilicate, Neusilin (registered trademark) US2 of Fuji Chemical Industry Co., Ltd. was used, as crystalline cellulose, CELPHERE (registered trademark) CP102 of Asahi Kasei Corporation was used, and as a mixture of lactose and crystalline cellulose, NONPAREIL (registered trademark) 105 of Freund Corporation was used. The results of the study are shown in Table 2.
[0066] [Table 2]
[0067]
[0068] The results in Table 2 show that when hydrated silica and magnesium aluminum silicate are used as core materials, a molten component layer can be formed on the surface because the core material is an adsorbent with fine pores, but other core materials cannot form a molten component layer on the surface and become paste-like, so it is difficult to form a molten component layer.
[0069] [Study of the first molten component]
[0070] In the manufacturing method of Example 1, the first molten component is changed to form a molten component layer on the surface of the core material. As the first molten component, polyethylene glycol 6000 (NOF Corporation, polyethylene glycol 6000 (P)), lauroyl alcohol (Nippon Surfactant Industries Co., Ltd.) or stearic acid (NOF Corporation, plant) is used. The results are shown in Table 3.
[0071] [Table 3]
[0072]
[0073] It was found that any oily additive that is solid at room temperature can form a molten component layer.
[0074] [Study of the Second Melt Component]
[0075] In the manufacturing method of Example 1, the second molten component was changed to form a drug-containing layer on the surface of the molten component layer. As the second molten component, stearic acid (NOF Corporation, plant), polyethylene glycol 6000 (NOF Corporation, polyethylene glycol 6000 (P)), and carnauba wax (Nippon Wax Co., Ltd., Polishing wax 105) were used. The results are shown in Table 4.
[0076] [Table 4]
[0077]
[0078] It was clarified that any oily additive that is solid at room temperature can form a drug substance-containing layer.
[0079] [Study of polymers used instead of the second molten component]
[0080] After mixing 1 g of the first molten component and 1 g of the polymer, the mixture was heated at 80°C for 2 hours. In addition, 2 g of the first molten component was also heated at 80°C for 2 hours, and the viscosity of the molten component without the mixed polymer and the molten component with the mixed polymer was evaluated by hand feel. As the molten component, lauroyl alcohol (Nippon Surfactant Industries Co., Ltd.), stearic acid (NOF Corporation) or hardened oil (Freund Corporation, Lubriwax) was used. In addition, as the polymer, aminoalkyl methacrylate copolymer E (Evonik, Eudragit (registered trademark) EPO), ammonium methacrylate copolymer RL (Evonik, Eudragit (registered trademark) RLPO), methacrylic acid copolymer L (Evonik, Eudragit (registered trademark) L100-55), hydroxypropyl methylcellulose acetate succinate (Shin-Etsu Chemical Co., Ltd., Shin-Etsu AQOAT (registered trademark) HPMC AS LF) or polyvinyl pyrrolidone (BASF, K30) was used.
[0081] The evaluation results are shown in Table 5.
[0082] [Table 5]
[0083]
[0084] ◎Viscosity increased significantly, ○Viscosity increased, ×No change, -Not evaluated.
[0085] Studies have shown that when lauromacrogol is used as a melting component, the viscosity of aminoalkyl methacrylate copolymer, ammonium alkyl methacrylate copolymer, methacrylic acid copolymer or hydroxypropyl methylcellulose acetate succinate increases, showing compatibility. In particular, methacrylic acid copolymer shows excellent compatibility with lauromacrogol. In addition, when stearic acid is used as a melting component, the viscosity of aminoalkyl methacrylate copolymer, ammonium alkyl methacrylate copolymer or polyvinyl pyrrolidone increases, showing compatibility. In particular, it is clear that aminoalkyl methacrylate copolymer and polyvinyl pyrrolidone show excellent compatibility with stearic acid. On the other hand, when hardened oil is used as a melting component, none of the polymers show compatibility.
[0086] [Example 3]
[0087] Here, it is investigated whether it is possible to produce particles by using a polymer that is compatible with the first molten component instead of the second molten component. 500.0 g of hydrated silica (Fuji Silysia Chemical Ltd., Sylopure (registered trademark) P100) was used as the core material, and 750.0 g of stearic acid (NOF Corporation, Plant) was used as the first molten component. The hydrated silica and stearic acid were placed in a high-speed stirring granulator (Fukae Industrial Co., Ltd., High-speed Mixer, FS-GS-5J), and granulated for 17 minutes under the conditions of a stirrer speed of 300 rpm, a chopper speed of 500 rpm, and a water temperature of 78.4°C to 82.6°C.
[0088] 160.0 g of the core material with the obtained molten component layer arranged on the surface, 496.4 g of sitagliptin phosphate as a raw material drug, and 48.0 g of aminoalkyl methacrylate copolymer E (Evonik, Eudragit EPO) as a polymer having good compatibility with the first molten component layer were put into a tumbling fluidized bed granulator (Powrex Corporation, MP-01), and granulation was carried out for 25 minutes at a rotor speed of 400 rpm and a gas supply temperature of 85° C. At this time, the temperature of the additive was 62° C.
[0089] The scanning electron microscope (SEM) images of the obtained particles are shown in Figure 5 (c) In addition, the particle size was measured. The particle size was measured using a laser diffraction / scattering method measuring device (Beckman Coulter Inc., LS 13 320). The measured particle size is D 10 =165.0μm, D 50 =207.0μm, D 90 =276.0μm.
[0090] In the granules of Example 3, the content ratio of the raw material drug is about 60%, and it is obvious that a high content of the raw material drug can be achieved.
[0091] [Example 4]
[0092] It was studied whether granules can be produced by using fexofenadine hydrochloride as a raw material drug instead of sitagliptin phosphate. 120.0 g of a core material having a molten component layer of Example 3 arranged on its surface, 240.0 g of fexofenadine hydrochloride as a raw material drug, and 40.0 g of methacrylic acid aminoalkyl ester copolymer E (Evonik, Eudragit EPO) as a polymer having good compatibility with the first molten component were put into a rotating fluidized bed granulator (Powrex Corporation, MP-01), and granulated for 45 minutes at a rotor speed of 400 rpm and a gas supply temperature of 80°C. At this time, the temperature of the additive was about 60°C.
[0093] The scanning electron microscope (SEM) images of the obtained particles are shown in Figure 5 (d) In addition, the particle size was measured. The particle size was measured using a laser diffraction / scattering method measuring device (Beckman Coulter Inc., LS 13 320). The measured particle size is D 10 =169.4μm, D 50 =215.3μm, D 90 =320.6μm.
[0094] [Comparative Example 1]
[0095] In order to explore whether the second molten component is necessary in the manufacture of granules with a high content of raw materials, we performed melt granulation without using the second molten component. 436g of hydrated silica (Fuji Silysia Chemical Ltd., Sylopure (registered trademark) P100) was used as the core material, and 654g of stearic acid (NOF Corporation, Plant) was used as the first molten component. The hydrated silica and stearic acid were placed in a high-speed stirring granulator (Fukae Industrial Co., Ltd., high-speed mixer, FS-GS-5J), and granulated for 15 minutes under the conditions of a stirrer speed of 300rpm, a chopper speed of 500rpm, and a water temperature of 75.7℃~78.5℃. At this time, the temperature of the additive was 69.1℃~71.9℃.
[0096] 40.0 g of the core material with the molten component layered on the surface and 124.1 g of sitagliptin phosphate as a raw material were put into a tumbling fluidized bed granulator (Powrex Corporation, MP-01) and granulated for 25 minutes at a gas supply temperature of 85.0° C. The temperature of the additive was 62° C. at this time.
[0097] The scanning electron microscope (SEM) images of the obtained particles are shown in Figure 5As shown in (e), since a molten component layer is disposed on the surface of the core material, although the API is slightly attached to the molten component layer, since there is no second molten component, it is not possible to obtain granules with a high API content.
[0098] [Comparative Example 2]
[0099] In order to explore whether the first molten component is necessary in the manufacture of granules with a high content of raw materials, we performed melt granulation without using the first molten component. The core material is hydrous silica (Fuji Silysia Chemical Ltd., Sylopure (registered trademark) P100), and the second molten component is aminoalkyl methacrylate copolymer E (Eudragit EPO, Evonik). 16g of hydrous silica, 12g of aminoalkyl methacrylate copolymer E and 124.1g of sitagliptin phosphate were put into a rotating fluidized bed granulator (Powrex Corporation, MP-01), and granulation was performed for 25 minutes at an air supply temperature of 85.0°C. At this time, the temperature of the additive was 62°C.
[0100] The scanning electron microscope (SEM) images of the obtained particles are shown in Figure 5 As shown in (f), since there is no first melt component, the API is not deposited on the core material at all.
[0101] (Explanation of Reference Numerals)
[0102] 10: particles; 11: core material; 13: molten component layer; 15: drug-containing layer;
[0103] 20: granules; 25: API layer; 131: first melting component; 151: API;
[0104] 153: second molten component; 253: polymer.
Claims
1. A particle, characterized in that include: Nuclear matter; a molten component layer disposed on the surface of the core material; and a drug-containing layer disposed on the surface of the molten component layer, Wherein, the core material is an adsorbent having pores on the surface, The molten component layer is disposed between the core material and the API-containing layer, contains a first molten component, and is a bottom layer that does not contain an API. The drug substance-containing layer contains the drug substance and a second melt component, The first molten component is selected from glycerol monostearate, polyethylene glycol, lauroyl alcohol and stearic acid, The second melting component is selected from the group consisting of stearic acid, glyceryl monostearate, polyethylene glycol, carnauba wax, hardened oil, lauromacrogol, palmitic acid and cetyl alcohol.
2. The particle according to claim 1, wherein The second molten component has a melting point lower than the melting point of the first molten component and 100° C. or lower.
3. The particle according to claim 1, wherein The second molten component has a melting point higher than the melting point of the first molten component and 100° C. or lower.
4. The particle according to claim 1, wherein The core material is spherical, The particle size of the core material is larger than the particle size of the API and the particle size of the second molten component.
5. The particle according to claim 1, wherein The molten component layer has a structure in which the first molten component is also arranged in the pores.
6. A particle, characterized in that include: Nuclear matter; a molten component layer disposed on the surface of the core material; and a drug-containing layer disposed on the surface of the molten component layer, Wherein, the core material is an adsorbent having pores on the surface, The molten component layer is disposed between the core material and the API-containing layer, contains a first molten component, and is a bottom layer that does not contain an API. The drug substance-containing layer contains a drug substance and a polymer that is compatible with the first molten component. The first melting component is stearic acid or lauromacrogol. When the first melting component is stearic acid, the polymer having compatibility is selected from the group consisting of aminoalkyl methacrylate copolymers, ammonioalkyl methacrylate copolymers and polyvinyl pyrrolidone. When the first melting component is lauromacrogol, the polymer having compatibility is selected from the group consisting of aminoalkyl methacrylate copolymers, ammonioalkyl methacrylate copolymers, methacrylic acid copolymers and hydroxypropyl methylcellulose acetate succinate.
7. The particle according to claim 6, wherein The molten component layer has a structure in which the first molten component is also arranged in the pores.
8. A preparation, characterized in that Include: The particle according to any one of claims 1 to 7; and One or more pharmaceutically acceptable additives.
9. The preparation according to claim 8, wherein The additive is a disintegrant.
Citation Information
Patent Citations
Method of producing solid dispersion
JP2015071542A
Production of granule
JP1994256169A
Granular solid preparation containing cephalosporin ester and production method thereof
JP2015199721A
Manufacturing method of medicine-containing particles, medicine-containing particles, pharmaceutical composition, and orally disintegrating tablet
JP2017001999A